Gas Pipeline Hydrodynamic Analysis Based on Beggs-Brill Correlation - Astyanto, Achilleus Hermawan (Media Teknika, 2016)
A reliable pipeline design requires hydrodynamic analysis. The analysis enables flow rate and pressure gradient investigations in obtaining an optimum configuration. In the other hand, a numerical approach occurs as a complex schematic is proposed. Solving this requirement, an iterative method is posible to be endorsed. This study aims to investigate single-phase gas pipeline hydrodynamic analysis. A model utilized a two-phase pressure gradient correlation, namely Beggs-Brill correlation, to converse single-phase gas pressure gradients into mass flow rates. Furthermore, the numerical method, called Newton-Raphson, is assesed on solving those iterative calculations. The results show that the model is able to solve a complex schematic. The mass flow rates obtain in the deviation up to 0.4 %, whereas the pressure gradients deviation is achieved on a higher value.Â